Great expectations - Dickens, Charles (Singapore Penguin Random House, 2024)
Pip, a blacksmith$1 (Bs apprentice goes from humble beginnings in the marshes of Kent to the bustling streets of Victorian London. A chance encounter with the escaped convict Magwitch sets off a series of events that lead Pip to the eccentric Miss Havisham and her captivating ward, Estella. In his pursuit of becoming a gentleman to win Estella$1 (Bs affection, Pip grapples with his own self-worth and the impact of his humble origins. Pip must unravel the complexities of his own identity and in the bustling 19th century London his idealistic ambitions are threatened by dominating class difference. Charles Dickens$1 (Briveting and thought-provoking novel raises profound questions about human worth and the pursuit of success in a rapidly changing world.s
Keywords: Fiction- English; Novel- English